2014
DOI: 10.1016/j.celrep.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channel Profile of TRPM8 Cold Receptors Reveals a Role of TASK-3 Potassium Channels in Thermosensation

Abstract: Summary Animals sense cold ambient temperatures through the activation of peripheral thermoreceptors that express TRPM8, a cold- and menthol-activated ion channel. These receptors can discriminate a very wide range of temperatures from innocuous to noxious. The molecular mechanism responsible for the variable sensitivity of individual cold receptors to temperature is unclear. To address this question, we performed a detailed ion channel expression analysis of cold sensitive neurons, combining BAC transgenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 71 publications
(126 reference statements)
3
84
0
Order By: Relevance
“…Although TASK3 channels have low overall levels of expression in DRG neurons and there is little evidence to show a role for them in general pain transduction, a recent study has suggested that these channels are highly enriched in TRPM8 positive neurons [72]. Since TASK3 knockout mice were found to have a hypersensitivity to cold stimuli, this suggests that TASK3 channels may have an important role in the transduction of painful cold stimuli [72].…”
Section: Twik1 and Task3 Channelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although TASK3 channels have low overall levels of expression in DRG neurons and there is little evidence to show a role for them in general pain transduction, a recent study has suggested that these channels are highly enriched in TRPM8 positive neurons [72]. Since TASK3 knockout mice were found to have a hypersensitivity to cold stimuli, this suggests that TASK3 channels may have an important role in the transduction of painful cold stimuli [72].…”
Section: Twik1 and Task3 Channelsmentioning
confidence: 96%
“…Since TASK3 knockout mice were found to have a hypersensitivity to cold stimuli, this suggests that TASK3 channels may have an important role in the transduction of painful cold stimuli [72].…”
Section: Twik1 and Task3 Channelsmentioning
confidence: 99%
“…For example, two-pore, nongated potassium channels contribute to cold pain as they are down-regulated after oxaliplatin treatment, thereby leading to enhanced neuronal excitability (61,62). Moreover, antagonism of the voltage-gated sodium channel Nav1.6 attenuated neuropathic cold allodynia (63).…”
Section: Discussionmentioning
confidence: 99%
“…A range of potassium channels, including the two-pore domain (2PK) background channels TRAAK, TASK-3, TREK-1, TRESK [118,119] as well as voltage-gated potassium channels K v 1 and K v 7.2/7.3, have been implicated in the physiology of cold sensing and the pathophysiology of cold pain. Closure of background 2PK channels underpins cooling-induced increase in excitability of cultured DRG neurons, leading to membrane depolarisation and increased firing [120,121].…”
Section: Potassium Channelsmentioning
confidence: 99%